Effect of Prudhoe Bay emissions on atmospheric aerosol growth events observed in Utqiaġvik (Barrow), Alaska. (March 2017) - Kolesar, Katheryn R.; Cellini, Jillian; Peterson, Peter K.; Jefferson, Anne; Tuch, Thomas; Birmili, Wolfram; Wiedensohler, Alfred; Pratt, Kerri A.
Abstract: The Arctic is a rapidly changing ecosystem, with complex aerosol-cloud-climate feedbacks contributing to more rapid warming of the region as compared to the mid-latitudes. Understanding changes to particle number concentration and size distributions is important to constraining estimates of the effect of anthropogenic activity on the region. During six years of semi-continuous measurements of particle number size distributions conducted near Utqiaġvik (Barrow), Alaska, 37 particle-growth events were observed. The majority of events occurred during spring and summer with a monthly maximum in June, similar to other Arctic sites. Based on backward air mass trajectory analysis, similar numbers of particle-growth events were influenced by marine (46%) and Prudhoe Bay air masses (33%), despite air primarily coming from the Arctic Ocean (75 ± 2% of days) compared to Prudhoe Bay (8 ± 2% of days). The corresponding normalized particle-growth event frequency suggests that emissions from Prudhoe Bay could induce an average of 92 particle-growth events, more than all other air mass sources combined, at Barrow annually. Prudhoe Bay is currently the third largest oil and gas field in the United States, and development in the Arctic region is expected to expand throughout the 21st century as the extent of summertime sea ice decreases. Elevated particle number concentrations due to human activity are likely to have profound impacts on climate change in the Arctic through direct, indirect, and surface albedo feedbacks, particularly through the addition of cloud condensation nuclei. Graphical abstract: Highlights: Prudhoe Bay oil field extraction emissions contribute to Arctic particle growth. An average of 8 particle-growth events occur per year in Barrow, AK. Particle-growth event frequency peaks in June and July.